A silicon-containing carbon-based negative electrode material and its preparation process and application

By using nitrogen/sulfur-doped microporous carbon material to coat nano-silicon in the lithium-ion battery negative electrode material, the structural instability problem caused by the volume change of the negative electrode material during the charge and discharge process in the existing technology is solved, and a higher Electrochemical performance and cycling stability.

CN118748246BActive Publication Date: 2025-01-21SHENZHEN MINGSHENG NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410890949.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-01-21
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The volume of existing lithium-ion battery anode materials such as graphite and silicon changes greatly during charging and discharging, resulting in unstable battery structure, affecting cycle life and performance, and poor conductivity.

Method used

Nano-silicon is coated with nitrogen/sulfur-doped microporous carbon material to form a shell-core coating structure, and nano-silicon is deposited in the pores of the microporous carbon material using a vapor deposition method.

Benefits of technology

It achieves improvements in electrochemical properties such as conductivity, specific capacity and cycle stability, prolongs the cycle life of the battery and improves charge and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118748246B_ABST
    Figure CN118748246B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials, and discloses a silicon-containing carbon-based negative electrode material and a preparation method and application thereof. The negative electrode material is prepared by depositing nano-silicon in the pores of a nitrogen / sulfur-doped microporous carbon material using a vapor deposition method, wherein the nitrogen / sulfur-doped microporous carbon material is prepared by using chemically cross-linked dextran aerogel as a carbon precursor and is prepared by carbonization. Since the chemically cross-linked dextran aerogel has a uniform and dense micro-nanoscale pore structure, the prepared nitrogen / sulfur-doped microporous carbon material can have high porosity and a large specific surface area. The material also contains miscellaneous elements doped therein, and the nano-silicon is coated with the aerogel as a coating material. The formed silicon-containing carbon-based negative electrode material has strong conductivity, good cycle stability, and high specific capacity, and can be used as an excellent negative electrode material for lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a silicon-containing carbon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery is a modern electrochemical energy storage technology with the advantages of high energy density, long life, environmental protection and recyclability. It is a widely used energy storage method in the fields of electric vehicles, mobile devices, etc. The working principle of lithium-ion battery is based on the migration and insertion / deinsertion reaction of lithium ions between the positive and negative electrodes. During the charging process, lithium ions are released from the positive electrode material, pass through the electrolyte and the separator, and migrate to the negative electrode material; during the discharge process, lithium ions are released from the negative electrode material, pass through the electrolyte and the separator, and migrate to the positive electrode material. In this process, electrons flow from the negative electrode to the positive electrode through the external circuit to form an electric current. Therefore, the choice of negative electrode material for lithium-ion batteries will have a decisive influence on the performance of lithium-ion batteries.

[0003] Graphite has good electrochemical properties and is widely available. It is often used as the negative electrode material for lithium-ion batteries. However, the gram capacity of graphite is insufficient to meet the actual needs of power lithium batteries. The theoretical capacity of silicon is much higher than that of carbon materials such as graphite, so it can provide higher energy density. However, during the charging and discharging process, the volume of silicon will change significantly, resulting in unstable battery structure, affecting the cycle life and performance of the battery, and silicon has poor conductivity. This will affect the charging and discharging rate and efficiency of the battery.

[0004] In order to overcome these shortcomings, the modification and optimization of silicon-based negative electrode materials are currently the focus of research. For example, the material properties are optimized by doping carbon-based graphite and modification methods, such as silicon-oxygen composite materials and silicon-carbon composite materials. Patent document CN109360946B provides a method for preparing a high compaction density silicon-carbon negative electrode material, specifically by mixing and coating silicon powder multiple times to form a high compaction density silicon-carbon negative electrode material with good specific capacity and cycle stability. Therefore, silicon and carbon materials can be combined to form a composite electrode material, which can solve the problems existing in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a silicon-containing carbon-based negative electrode material and its preparation method and application. By using nitrogen / sulfur-doped microporous carbon material to coat nanosilicon, a negative electrode material with good electrochemical properties such as conductivity, specific capacity and cycle stability can be obtained.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A silicon-containing carbon-based negative electrode material having a core-shell coating structure; the shell layer material is a nitrogen / sulfur-doped microporous carbon material; the core layer material is nano-silicon;

[0008] The negative electrode material is prepared by depositing nano-silicon in the pores of a sulfur-doped microporous carbon material using a vapor deposition method.

[0009] Further preferably, the nitrogen / sulfur doped microporous carbon material is prepared by the following method:

[0010] Step 1: Preparation of dextran gel

[0011] Nitrogen is introduced into the reaction kettle to exclude oxygen, and dextran and N, N-dimethylformamide are added to the reaction kettle in sequence, and mechanical stirring is performed to mix them evenly. Under ice bath conditions, diformyl chloride monomer compounds are added to the reaction kettle, and after the addition is completed, stirring is performed at room temperature for 6-8 hours. Thiophene monomer compounds and accelerators are continuously added to the reaction kettle, and stirring is continued for 9-12 hours, and then stirring is stopped and the mixture is allowed to stand to obtain dextran gel material;

[0012] Step 2: Preparation of dextran aerogel

[0013] Pour the dextran gel into a mold and transfer it to a freeze dryer. After freeze drying at -50°C for 24-48 hours, place it in a vacuum dryer at 50°C for 12-24 hours, grind it to obtain dextran aerogel.

[0014] Step 3: Preparation of nitrogen / sulfur doped microporous carbon materials

[0015] The nitrogen / sulfur doped microporous carbon material is placed in a tubular furnace, argon gas is introduced for protection, and the temperature is increased for calcination to obtain the nitrogen / sulfur doped microporous carbon material.

[0016] Further preferably, the molecular weight of the dextran is 40 kDA.

[0017] More preferably, the dicarboxylic acid chloride monomer compound is 2,6-pyridinedicarboxylic acid chloride.

[0018] More preferably, the thiophene monomer compound is thiophene-2,5-diyldimethanol.

[0019] More preferably, the promoter is triethylamine or pyridine.

[0020] Further preferably, during the heating process, the heating rate is set at 3-5°C / min, the temperature is raised to 650-800°C, and the calcination is performed for 1-3h.

[0021] In the above technical scheme, the possible mechanism is: dextran contains a large number of hydroxyl groups, and the diformyl chloride monomer compound is used as a bridge. Through the bridging effect of the diformyl chloride monomer compound, a condensation reaction first occurs with dextran to cross-link the dextran to form a dextran molecule with a cross-linked structure. Under the action of the promoter, the residual acyl chloride groups in the cross-linked structure dextran molecules can further condense with the hydroxyl groups in the thiophene monomer compound to make the cross-linked structure more compact, forming a dextran gel material with pyridine molecules as the cross-linking center and containing thiophene groups in the structure. After freeze-drying and vacuum drying, a dextran aerogel can be formed. Due to the presence of the cross-linked structure, the dextran aerogel contains a large number of micro-nano-level pore structures. After high-temperature calcination and carbonization, a microporous carbon material with rich micro-nano pores can be formed. During the carbonization process, the pyridine group and the thiophene group will exist in the microporous carbon material in the form of element doping to form a nitrogen / sulfur-doped microporous carbon material.

[0022] A method for preparing a silicon-containing carbon-based negative electrode material is as follows:

[0023] Place the nitrogen / sulfur doped microporous carbon material in a tubular furnace, introduce a mixed gas of monosilane, hydrogen and argon, raise the temperature of the tubular furnace to 1100-1200°C, deposit nanosilicon inside the pores of the nitrogen / sulfur doped microporous carbon material, stop heating after 48-72 hours, take out the material, and wait for it to cool naturally to obtain a silicon-containing carbon-based negative electrode material.

[0024] Further preferably, in the mixed gas of monosilane, hydrogen and argon, the volume ratio of monosilane, hydrogen and argon is 3-5:10:10.

[0025] In the above technical scheme, by adopting the vapor deposition method, monosilane is used as the raw material. When it passes through the pores of the nitrogen / sulfur-doped microporous carbon material, it will be deposited in the pores and gradually grow to form nano-silicon. Since the pore structure of the nitrogen / sulfur-doped microporous carbon material is at the micro-nano level, the silicon particles can only grow into nano-scale silicon in the end, and finally a silicon-containing carbon-based negative electrode material is obtained.

[0026] An application of a silicon-containing carbon-based negative electrode material, applying the silicon-containing carbon-based negative electrode material in the field of electrode materials for lithium-ion batteries.

[0027] Beneficial effects of the present invention:

[0028] 1) The present invention uses chemically cross-linked dextran aerogel as a carbon precursor to prepare nitrogen / sulfur-doped microporous carbon materials. Since the chemically cross-linked dextran aerogel has a uniform and dense micro-nanoscale pore structure, these pore structures can be effectively retained during the carbonization process, so that the prepared nitrogen / sulfur-doped microporous carbon materials also have uniform micro-nanoscale pores, so the specific surface is larger, there are more active lithium storage sites, and thus can show a higher specific capacity, and the micro-nanoscale pores can shorten the diffusion path of lithium ions, accelerate the transmission and transfer of lithium ions, and make the negative electrode material show more excellent electrochemical performance. In addition, nitrogen doping can introduce defect structures such as pyridine nitrogen, so that the conductivity of the microporous carbon material is further improved, and sulfur doping can further increase the specific surface area of ​​the microporous carbon material, so as to have a better specific capacity performance.

[0029] 2) The present invention uses a vapor deposition method to deposit silicon in the pores of nitrogen / sulfur-doped microporous carbon materials. Under the confinement of micro-nano-scale pores, silicon particles can only grow to the size of the pores to form nano-scale silicon particles. Nano-silicon has a larger specific surface area, can expose more electrochemical active sites, participate in redox reactions, accelerate the electrochemical reaction process, and make lithium-ion batteries more efficient. Moreover, after being wrapped in carbon materials, the volume expansion of nano-silicon can also be weakened, and the problem of poor conductivity can also be fully solved. Therefore, the prepared silicon-containing carbon-based negative electrode material has good electrochemical properties such as conductivity and cycle stability.

[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1 This is a scanning electron microscope image of the dextran aerogel in Example 1 of the present invention;

[0033] Figure 2 These are electron microscope images of the nitrogen / sulfur doped microporous carbon material in Example 1 of the present invention, wherein (A) is a scanning electron microscope image and (B) is a transmission electron microscope image. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A silicon-containing carbon-based negative electrode material is prepared by the following preparation method:

[0037] Place the nitrogen / sulfur doped microporous carbon material in a tubular furnace, introduce a mixed gas of monosilane, hydrogen and argon in a volume ratio of 3:10:10, raise the temperature of the tubular furnace to 1100°C, deposit nanosilicon inside the pores of the nitrogen / sulfur doped microporous carbon material, stop heating after 48 hours, take out the material, and wait for it to cool naturally to obtain a silicon-containing carbon-based negative electrode material.

[0038] The nitrogen / sulfur doped microporous carbon material is prepared by the following method:

[0039] Step 1: Preparation of dextran gel

[0040] Nitrogen was introduced into the reaction kettle to exclude oxygen, and 1.5 g of dextran with a molecular weight of 40 kDA and N, N-dimethylformamide were added to the reaction kettle in sequence, and the mixture was evenly mixed by mechanical stirring. Under ice bath conditions, 3.5 g of 2,6-pyridinedicarbonyl chloride was added to the reaction kettle, and after the addition was completed, the mixture was stirred at room temperature for 6 h. 0.8 g of thiophene-2,5-diyldimethanol and 1 g of triethylamine were continuously added to the reaction kettle, and the mixture was stirred for 12 h, then the stirring was stopped and the mixture was allowed to stand to obtain a dextran gel.

[0041] Step 2: Preparation of dextran aerogel

[0042] The dextran gel material is poured into a mold and transferred to a freeze dryer. After freeze drying at -50°C for 48 hours, it is placed in a vacuum dryer at 50°C for 24 hours, and ground to obtain dextran aerogel.

[0043] The morphology of the dextran aerogel was observed using a JSM-6700F field emission scanning electron microscope. Figure 1 It can be clearly observed that the dextran aerogel has a very dense structure and a very uniform and rich micro-nanoscale pore structure. Using it as a carbon precursor can make the prepared carbon material have a richer pore structure.

[0044] Step 3: Preparation of nitrogen / sulfur doped microporous carbon materials

[0045] The nitrogen / sulfur doped microporous carbon material is placed in a tubular furnace, argon gas is introduced for protection, the heating rate is controlled to be 4°C / min, the temperature is increased to 750°C, and calcined for 2h to obtain the nitrogen / sulfur doped microporous carbon material.

[0046] The nitrogen / sulfur doped microporous carbon material was analyzed using a JSM-6700F field emission scanning electron microscope and a JEM2100 high resolution transmission electron microscope. Figure 2 , where (A) is a scanning electron microscope image, and (B) is a transmission electron microscope image. It can be observed from (A) that the microporous carbon material has a rich micro-nanoscale pore structure, and it can be observed from (B) that the carbon material contains nano-silicon particles.

[0047] Example 2

[0048] A silicon-containing carbon-based negative electrode material is prepared by the following preparation method:

[0049] The nitrogen / sulfur-doped microporous carbon material prepared in Example 1 of the present invention is placed in a tubular furnace, and a mixed gas of monosilane, hydrogen and argon with a volume ratio of 4:10:10 is introduced. The temperature of the tubular furnace is raised to 1150°C, and nano-silicon is deposited inside the pores of the nitrogen / sulfur-doped microporous carbon material. After 60 hours, the heating is stopped, the material is taken out, and it is allowed to cool naturally to obtain a silicon-containing carbon-based negative electrode material.

[0050] Example 3

[0051] A silicon-containing carbon-based negative electrode material is prepared by the following preparation method:

[0052] The nitrogen / sulfur-doped microporous carbon material prepared in Example 1 of the present invention is placed in a tubular furnace, and a mixed gas of monosilane, hydrogen and argon with a volume ratio of 5:10:10 is introduced. The temperature of the tubular furnace is raised to 1200°C, and nano-silicon is deposited inside the pores of the nitrogen / sulfur-doped microporous carbon material. After 72 hours, the heating is stopped, the material is taken out, and it is allowed to cool naturally to obtain a silicon-containing carbon-based negative electrode material.

[0053] Comparative Example 1

[0054] A silicon-containing carbon-based negative electrode material is prepared by the following preparation method:

[0055] The porous carbon material is placed in a tubular furnace, and a mixed gas of monosilane, hydrogen and argon in a volume ratio of 4:10:10 is introduced. The temperature of the tubular furnace is raised to 1150°C, and nano-silicon is deposited inside the pores of the nitrogen / sulfur-doped microporous carbon material. The heating is stopped after 60 hours, the material is taken out, and it is allowed to cool naturally to obtain a silicon-containing carbon-based negative electrode material.

[0056] The porous carbon material is prepared by the following method:

[0057] Dextran and potassium hydroxide in a mass ratio of 1:4 are placed in a tubular furnace, argon gas is introduced for protection, the heating rate is controlled at 4°C / min, the temperature is increased to 7500°C, and calcined for 2 hours to obtain the product.

[0058] a. The conductivity of the nitrogen / sulfur doped microporous carbon material prepared in Example 1 of the present invention and the porous carbon material prepared in Comparative Example 1 was tested using a DDSJ conductivity tester; the specific surface area and pore structure of the nitrogen / sulfur doped microporous carbon material prepared in Example 1 of the present invention and the porous carbon material prepared in Comparative Example 1 were tested using a BSD specific surface area and micropore analyzer. The test results are recorded in the following table:

[0059] project Conductivity (S / cm) <![CDATA[Specific surface area (m 2 / g)]]> Pore ​​size (nm) Example 1 3.29 1828.4 2.981 Comparative Example 1 2.61 895.9 6.249

[0060] From the test results in the analysis table, it can be seen that the nitrogen / sulfur-doped microporous carbon material prepared in Example 1 of the present invention has stronger conductivity, larger specific surface area, and finer pore structure. This is because the dextran aerogel formed by chemical cross-linking has a dense structure and more abundant and uniform pores, and the nitrogen doping in its structure can introduce a defect structure and enhance its conductivity.

[0061] b. Weigh 75g of silicon-containing carbon-based negative electrode materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1 respectively, mix them evenly with 15g of acetylene black conductive agent and 10g of sodium carboxymethyl cellulose binder, add N-methyl pyrrolidone dropwise and stir, and after forming a uniform material, coat it on aluminum foil, and after curing completely at 80°C, take it out and make it into a negative electrode sheet with a diameter of 10mm. Use lithium hexafluoroborate with a concentration of 1M as the electrolyte and Celgard2500 type diaphragm to assemble it into a button cell in a glove box filled with argon. After the assembled button half-cell is left for 12h, a constant current charge and discharge cycle test is carried out at a voltage range of 0.1-1.5V. The test current density is 0.1A / g. The test results are shown in the following table:

[0062] project Initial discharge capacity (mAh / g) Capacity retention after 100 cycles (%) Example 1 1850.8 92.1 Example 2 1869.4 92.2 Example 3 1868.1 92.1 Comparative Example 1 1482.3 86.8

[0063] From the test results in the analysis table, it can be seen that the nitrogen / sulfur-doped microporous carbon material prepared in Example 1 of the present invention is used as a coating material to coat nano-silicon, and the formed silicon-containing carbon-based negative electrode material has an initial discharge specific capacity of up to 1869.4 mAh / g, and a capacity retention rate of up to 92.2% after 100 cycles. It has good specific capacity performance and cycle stability, and can be used as an excellent negative electrode material for lithium-ion batteries.

[0064] In contrast, in Comparative Example 1, the porous carbon material used is formed by carbonization of uncross-linked modified dextran as a precursor, so it does not contain nitrogen and sulfur doping, and has a relatively loose structure, large pores, and a low specific surface area, which cannot effectively coat nano-silicon. Therefore, the specific capacity and cycle stability of the prepared silicon-containing carbon-based negative electrode material are not as good as those of the silicon-containing carbon-based negative electrode material prepared in the embodiment.

[0065] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0066] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A silicon-containing carbon-based negative electrode material, characterized in that: The negative electrode material has a core-shell coating structure; The negative electrode material is prepared by depositing nano-silicon in the pores of nitrogen / sulfur-doped microporous carbon material using a vapor deposition method; The nitrogen / sulfur doped microporous carbon material is prepared by the following method: Step 1: Preparation of dextran gel Nitrogen is introduced into the reaction kettle to exclude oxygen, and dextran and N,N-dimethylformamide are added to the reaction kettle in sequence, and mechanical stirring is performed to mix them evenly. Under ice bath conditions, diformyl chloride monomer compounds are added to the reaction kettle, and after the addition is completed, stirring is performed at room temperature for 6-8 hours. Thiophene monomer compounds and accelerators are continuously added to the reaction kettle, and stirring is continued for 9-12 hours, and then stirring is stopped and the reaction kettle is allowed to stand to obtain dextran gel material; Step 2: Preparation of dextran aerogel Pour the dextran gel into a mold and transfer it to a freeze dryer. After freeze drying at -50°C for 24-48 hours, place it in a vacuum dryer at 50°C for 12-24 hours, grind it to obtain dextran aerogel. Step 3: Preparation of nitrogen / sulfur doped microporous carbon materials The dextran aerogel is placed in a tubular furnace, argon gas is introduced for protection, and the temperature is raised for calcination to obtain a nitrogen / sulfur-doped microporous carbon material; The dicarboxylic acid chloride monomer compound is 2,6-pyridine dicarboxylic acid chloride; The thiophene monomer compound is thiophene-2,5-diyldimethanol.

2. The silicon-containing carbon-based negative electrode material according to claim 1, characterized in that: In the first step, the molecular weight of the dextran is 40 kDA.

3. The silicon-containing carbon-based negative electrode material according to claim 1, characterized in that: In the first step, the promoter is triethylamine or pyridine.

4. The silicon-containing carbon-based negative electrode material according to claim 1, characterized in that: In the third step, during the heating process, the heating rate is set to 3-5°C / min, the temperature is raised to 650-800°C, and calcined for 1-3h.

5. The method for preparing a silicon-containing carbon-based negative electrode material according to claim 1, characterized in that: The preparation method is as follows: Place the nitrogen / sulfur doped microporous carbon material in a tubular furnace, introduce a mixed gas of monosilane, hydrogen and argon, raise the temperature of the tubular furnace to 1100-1200°C, deposit nanosilicon inside the pores of the nitrogen / sulfur doped microporous carbon material, stop heating after 48-72 hours, take out the material, and wait for it to cool naturally to obtain a silicon-containing carbon-based negative electrode material.

6. The method for preparing a silicon-containing carbon-based negative electrode material according to claim 5, characterized in that: In the mixed gas of monosilane, hydrogen and argon, the volume ratio of monosilane, hydrogen and argon is 3-5:10:

10.

7. The use of a silicon-containing carbon-based negative electrode material according to claim 1, characterized in that: The silicon-containing carbon-based negative electrode material is applied in the field of electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Multiple-coating high-density silicon-carbon anode material and its preparation method

    CN109360946B

  • Preparation method and application of lithium carbonate coated heteroatom doped silicon-carbon composite material

    CN117913255A

  • Negative electrode material, preparation method thereof and battery

    CN118231635A